ANALYSIS OF UZBEKISTAN’S PROSPECTIVE INVESTMENT ATTRACTION PLAN TODAY (Conferencea, 2023)
In recent years, intensive, qualitatively new structural and deep market reforms have been taking place in the economy of Uzbekistan, the priorities of the country’s socio-economic development are being fundamentally revised, and new, practical drivers of economic growth, which have the power to actually move the economy, are being introduced. Old, ineffective institutions and economic regulatory tools are giving way to new, innovative and effective forms and methods of influencing the economy. Considering the multiplicity of effectiveness (that is, not only money, but capital in the form of leading technologies, effective marketing and advanced management experience) in attracting foreign investments to the economy, and understanding that its importance and volume are significant, we will consider foreign direct investments in particular. Foreign loans and investments under government guarantee, with full transfer of risk to the recipient, are difficult to equate to direct investment. Moreover, such investments are not always accompanied by new technologies, effective marketing and advanced management experience. Most importantly, we believe that the country should not attract foreign investments under the guaranty of the government, because this violates the principle of social responsibility of generations, that is, “those who live now consume, and future generations pay for it. [1]”